(untitled) (Research, Society and Development, 2020)
A pandemic caused by the “new coronavirus” has caused a impact in the lives of people, health systems, public health programs and economies around the world, so that the efforts of the scientific community and official public health agencies are intense in the search guidelines and research to contain the advances and aggravations caused by this serious health problem. Therefore, the objective of this work was to identify and analyze the publications of protocols and guidelines for coping with the infection by the new Coronavirus (Sars-CoV-2) in Brazil. The search was performed in the PubMed / Medline, Scopus, Lilacs and Scielo databases and, mainly, by manual search on official websites in Brazil. The selected documents were published in 2020, until June 9. 113 documents were selected for the qualitative synthesis. Of these, recommendations on support measures were the most frequent theme in the studies, followed by the use of personal protective equipment (PPE), diagnostic exam documents and, finally, guidance on pharmacological treatment. This scope review gathered recommendations related to the clinical management of patients diagnosed with COVID-19 in Brazil. In this context, it was possible to observe the performance of official bodies (ANVISA, MS and PAHO) and institutions (Societies, Councils, Universities and Associations) aimed at the production of technical documents.